(untitled) (Physical Education, Health and Social Sciences, 2025)
Cardiovascular disease (CVD) is a leading cause of death around the world including Pakistan. The patients’ knowledge about cardiac risk factors is crucial for the effective management of modifiable risk factors. To assess knowledge and attitude regarding cardiovascular disease risk and prevention in patient with coronary artery disease. It was descriptive, quantitative, cross-sectional study in nature in which 50 patient diagnosed with coronary artery disease included from the CCU of Institute of Cardiology. Self-administered questionnaires were used to collect the data from the participants. Total 50 participants appeared having age range 35 years to 55 years old. Only 44% respondents knew that they suffered from coronary artery disease and remaining 46% didn’t. 14% reported that CAD (Coronary Artery Disease) was the leading cause of death and remaining 86% hadn’t any idea about it. Overall, 64% participants showed low level of knowledge; 20% participants moderate level and only 16% participants showed high level of knowledge regarding CVD risks and prevention. On the other hand, 40% participants showed low level of attitude; 28% moderate and 32% showed high level of attitude regarding CVD. In conclusion, low level of knowledge found among the study participants regarding cardiovascular disease in patients with coronary artery disease whereas attitude was slightly better than knowledge.